2011
DOI: 10.1371/journal.pone.0018317
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Structure and Function Are Disrupted by Standard Isolation Methods

Abstract: Mitochondria regulate critical components of cellular function via ATP production, reactive oxygen species production, Ca2+ handling and apoptotic signaling. Two classical methods exist to study mitochondrial function of skeletal muscles: isolated mitochondria and permeabilized myofibers. Whereas mitochondrial isolation removes a portion of the mitochondria from their cellular environment, myofiber permeabilization preserves mitochondrial morphology and functional interactions with other intracellular componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
252
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(265 citation statements)
references
References 51 publications
8
252
1
Order By: Relevance
“…One of the primary benefits of using the permeabilized myofiber technique is the preservation of mitochondrial structure and content with this method (Saks et al, 1998;Picard et al, 2011). In addition, we have also found that routine mitochondrial isolation methods markedly exaggerate the degree of mitochondrial dysfunction in severely atrophied aging muscle (Picard et al, 2010).…”
Section: Significance Of Measures In Permeabilized Myofibersmentioning
confidence: 81%
“…One of the primary benefits of using the permeabilized myofiber technique is the preservation of mitochondrial structure and content with this method (Saks et al, 1998;Picard et al, 2011). In addition, we have also found that routine mitochondrial isolation methods markedly exaggerate the degree of mitochondrial dysfunction in severely atrophied aging muscle (Picard et al, 2010).…”
Section: Significance Of Measures In Permeabilized Myofibersmentioning
confidence: 81%
“…However, the interpretation of the results obtained by Campbell et al [24] presents some difficulties. First, it is possible that isolated mitochondria and permeabilized muscle fibre preparations show different functional properties as reported in vertebrates [61]. A recent study on mosquitoes does not support this possibility as the two preparations responded similarly to various substrates, including proline [48].…”
Section: Discussion (A) Proline Metabolism In Hymenopteransmentioning
confidence: 95%
“…Studies carried out on rat muscle (permeabilised fibres and isolated mitochondria) or liver or in cell lines may not be representative of skeletal muscle from human patients with type 2 diabetes. Recently, it has also been reported that fundamental differences exist in the respiratory responses of isolated mitochondria and permeabilised fibres [23].…”
Section: Discussionmentioning
confidence: 99%